Effects of different weight loss protocols on serum leptin levels in obese females - Ozcelik, O; Dogan, H; Celik, H; Ayar, A; Serhatlioglu, S; Kelestimur, H (Acad Sciences Czech Republic, Inst Physiology, 2005)
We investigated the effects of different weight loss protocols on leptin levels in obese females with the aim of addressing the leptin resistance which has been found to be an aggravating factor in obesity. Twenty-four obese females enrolled to one of three 12-week weight loss protocols: orlistat-induced weight loss (OWL, n=8), exercise-induced weight loss (EWL, n=8) and orlistat plus exercise-induced weight loss (OEWL, n=8). Serum leptin levels were measured in duplicate by radioimmunoassay. There were significant reductions (P < 0.01) in body weight and fat mass after the 12 week period in all groups: -11.4 +/- 0.5 kg and -9.8 +/- 0.5 kg (OEWL), -8.3 +/- 0.8 kg and -5.7 +/- 0.9 kg (OWL), -8.9 +/- 1.2 kg and -7.4 +/- 1.2 kg (EWL), respectively. Serum leptin levels were also decreased markedly in all groups: -59.2% (OEWL1), -37.8% (OWL) and -48.6% (EWL) (P < 0.01 all). In addition, there were marked decreases in leptin levels for each kilogram of fat mass after the 12 week period: -48.2 +/- 7.2% (OEWL), -27.8 +/- 4.8% (OWL) and -39.3 +/- 4.3% (EWL) (P < 0.01 all). Decreases in serum leptin levels expressed per kilogram of fat mass were significantly higher in the OEWL group compared to the OWL group (P=0.03). Consequently, an exercise training program in adjunct to pharmacotherapy provides higher weight reduction and fat mass loss in obesity treatment. It also seems to have further beneficial effects on leptin resistance, as indicated by decreases in leptin levels expressed per kilogram of fat mass.
Keywords: leptin; exercise; obesity; pharmacotherapy; weight loss